An Assessment of the Impact of External Debt on Economic Growth of Nepal - Bhatta, Gunakar (NRB Economic Review, 2003)
Countries at early stages of development have small stocks of capital and require foreign borrowing for their investment needs and meet their external resource gap. Nepal's dependence on foreign assistance, nearly for the last five decades, can be viewed from the same perspective. The present article is a preliminary work in the direction of analyzing the relationship of external debt and economic growth of Nepal. The examination of debt burden indicators suggests the increasing burden of external debt, with a significant increase in the size and magnitude of such debt during 1990s. The empirical observation shows the external debt flow having positive effect on economic growth. This indicates that external debt should not be viewed only as a burden but also as a major source of financing for a developing economy like Nepal. However, the analysis of external debt stock and debt servicing shows that the equally important that external borrowing be made to supplement but not replace domestic savings in the long run.